2017
DOI: 10.3892/ol.2017.6748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of FABP5 gene silencing on the proliferation, apoptosis and invasion of human gastric SGC-7901 cancer cells

Abstract: The aim of the present study was to examine the effect of fatty acid binding protein-5 (FABP-5) gene on the proliferation, apoptosis and invasion of human gastric cancer SGC-7901 cells. The viability, apoptosis and cell invasion of SGC-7901 cells before and after FABP5 knockdown were taken as the study objects, design and synthesis of siRNA interference sequence were conducted according to FABP-5 mRNA coding sequences, and SGC-7901 cells were transiently transfected. The human gastric cancer SGC-7901 cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
1
18
0
1
Order By: Relevance
“…Similar results have been obtained in human cells. The silence of FABP5 gene made effects on the proliferation, apoptosis and invasion of human gastric SGC-7901 cancer cells [29]. Above results from previous studies supported that the IRGs screened with our method showed clinical significance.…”
Section: Discussionsupporting
confidence: 81%
“…Similar results have been obtained in human cells. The silence of FABP5 gene made effects on the proliferation, apoptosis and invasion of human gastric SGC-7901 cancer cells [29]. Above results from previous studies supported that the IRGs screened with our method showed clinical significance.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, FABP5, which promotes tumor cell growth in cervical cancer, was identified as a potential biomarker for lymph node metastasis ( 18 , 19 ). FABP5 gene silencing inhibited the proliferation and invasion of human SGC-7901 gastric cancer cells in vitro ( 20 ), and FABP5 stimulated hepatocellular carcinoma progression and metastasis via EMT ( 21 ). Considering the pivotal functions of the PI3K/AKT signaling pathway in tumor cells, particularly ccRCC cells, we hypothesized that FABP5 may affect ccRCC cell function via the PI3K/AKT signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the upregulation of FABP5 stimulates fatty acid transport, which finally induces cell growth and survival [44]. It was also presented that the silence of the FABP5 gene might attenuate the invasiveness of gastric cancer cells, detain cell proliferation, and arrest the cell cycle in the G0/ G1 phase, leading to a significant increase in apoptosis [45]. BMS309403 is a well-designed inhibitor of FABPs (FABP3-5, and −7), which interacts with the fatty acid-binding pocket to inhibit the binding of fatty acids [23,46].…”
Section: Discussionmentioning
confidence: 99%